Nanopartículas de PMMA obtidas por polimerização em miniemulsão via emulsão dupla para encapsulamento de biomoléculas - Cunha, Natali Altoé da (2018)
In situ miniemulsion polymerizations allows for formation of polymer nanoparticles very attractive to the pharmaceutical market, because the technique is capable of encapsulating various therapeutic actives. When these drugs are hydrophilic, double miniemulsion polymerization seems to be the most appropriate technique. Therefore, this work aimed to prepare stable water-oil-water (W/O/W) double emulsions, suitable for polymerization of methyl methacrylate monomer for the encapsulation and release of water-soluble drugs. Process scaling up was also pursued by high pressure homogenizer. Emulsions were characterized in terms of stability and morphology and the produced nanoparticles by morphology, size, molar mass, kinetic behavior and thermal stability, encapsulation efficiency and release of BSA protein, used as a model drug. The obtained results showed that the proposed procedure provided stable emulsions and promising nanoparticles. The properties obtained with the homogenizer and ultra-turrax were similar. The incorporation of BSA did not affect the characteristics of the nanoparticles significantly and led to considerable encapsulation efficiencies, close to 64% and 90% using turrax and homogenizer, respectively. Thus, the obtained results indicated that the proposed methodology has great potential for development in pharmaceutical applications.